2019
DOI: 10.1074/jbc.ra119.009955
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the combinatorial effects of antimicrobial peptides reveal a role of aromatic–aromatic interactions in antibacterial synergism

Abstract: Edited by Wolfgang PetiThe recent development of plants that overexpress antimicrobial peptides (AMPs) provides opportunities for controlling plant diseases. Because plants employ a broad-spectrum antimicrobial defense, including those based on AMPs, transgenic modification for AMP overexpression represents a potential way to utilize a defense system already present in plants. Herein, using an array of techniques and approaches, we report on VG16KRKP and KYE28, two antimicrobial peptides, which in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…The combination of magainin 2 and tachyplesin 1 also enhances the bacterial membrane recognition by constituting the oligomeric structures before contacting the anionic bacterial membrane surface [ 378 ]. In addition, a recent study from Bhunia’s group reported that two AMPs, VG16KRKP and KYE28, exhibited synergistic antimicrobial effects against plant pathogens and proteases through formatting an unusual peptide complex [ 379 ].…”
Section: Drug Combinationmentioning
confidence: 99%
“…The combination of magainin 2 and tachyplesin 1 also enhances the bacterial membrane recognition by constituting the oligomeric structures before contacting the anionic bacterial membrane surface [ 378 ]. In addition, a recent study from Bhunia’s group reported that two AMPs, VG16KRKP and KYE28, exhibited synergistic antimicrobial effects against plant pathogens and proteases through formatting an unusual peptide complex [ 379 ].…”
Section: Drug Combinationmentioning
confidence: 99%
“…Three-D structures of AMPs can be determined in solutions of LPS micelles using tr-NOESY NMR [ 61 , 62 , 63 , 64 ]. Also, the LPS-interacting residues of AMPs are determined at atomic resolution by STD-NMR [ 65 , 66 , 67 , 68 ].…”
Section: Atomic-resolution Structure Of Thanatin In Lps Outer Membmentioning
confidence: 99%
“…[19][20] AMPs are present ubiquitously in nature as the first line of defence in several life forms from invertebrates to the plants or mammals. [21][22][23][24] Natural AMPs show broad-spectrum antimicrobial activity against microbes like bacteria, fungi, protozoa and even several classes of pathologically relevant viruses. [25] AMPs have an additional strength over the conventional antibiotics in having diverse modes of action in contrast to the fixed intracellular targets for antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…AMPs are present ubiquitously in nature as the first line of defence in several life forms from invertebrates to the plants or mammals [21–24] . Natural AMPs show broad‐spectrum antimicrobial activity against microbes like bacteria, fungi, protozoa and even several classes of pathologically relevant viruses [25] .…”
Section: Introductionmentioning
confidence: 99%